The cooling of the pressing device in the glass industry - Salac, P; Stary, M (The International Journal of Multiphysics, 2013)
In this article we investigate the problem of shape optimization of the cooling cavity of the plunger used in the forming process in the glass industry. A rotationally symmetrical system consisting of the mould, the glass piece, the plunger and the plunger cavity is considered. The state problem is given as a stationary head conduction equation. The system has a given heat source which represents the glass piece and is cooled by flowing water inside the plunger cavity and by the environment of the mould on the outside. The design variable is taken to be the shape of inner surface of the plunger cavity. According to the results of the verification experiments, it is possible to claim that the numerical optimization that was achieved brought about a significant improvement. Further an unsteady periodic experiment representing the cyclical movement in a realistic working mode was performed to examine the effect of replacing it with the static model.